Analysis of religious coping relationships with family resilience in utilizing socio-economic resources during the COVID-19 pandemic - Yoyok Bekti Prasetyo; Faridi Faridi; Nur Lailatul Masruroh; Nur Melizza; Siska Sufianti Safitri (Jurnal Keperawatan Padjadjaran, 2023)
Background: Religious coping has a very important role in overcoming difficult problems in the family. The purpose of this study was to determine the relationship between religious coping with family resilience in utilizing socioeconomic resources during the COVID-19 pandemic. Method: The research design used was analytical descriptive with a cross-sectional approach. The respondents in this study were 242 villagers in East Java Province. Data were collected by SWBS for religious coping and FRAS for family resilience. Data analysis used logistic regression. Results: Factors that influence family resilience in utilizing socioeconomic resources involve religious coping. Families that have adequate religious coping will have a greater opportunity to have resilience in communication and problem-solving compared to families with inadequate religious coping (OR: 1.081; 95% CI: 1.038 - 1.127). Conclusion: Family resilience in utilizing socioeconomic resources is strongly influenced by religious coping factors. Strengthening the community with a religious approach is needed to support the family's line of defense against this pandemic condition.